Occupational choice and agricultural labour efficiency in Nigeria: Impact of ICTs - Etowa, Egbe Bassey; Adejo, Olugbenga Wilson (Applied Studies in Agribusiness and Commerce, 2017)
Increased labour efficiency is imperative in the developing world and particularly in Nigerian Agriculture which should be in its leaping phase. The interaction between labour efficiency and ICTs is inevitable in the realisation of the nation’s agribusiness potentials. Following a vivid descriptive statistics on main occupations and access to ICTs among the Nigerian populace, this study assessed effects of ICTs on the probability that a working aged Nigerian chose agricultural occupation over non-agricultural occupations. In doing so, the study analysed the effects of access to ICTs on agricultural labour efficiency in Nigeria. Data used for the analysis were drawn from the Nigerian General Household Survey-Panel held in 2010-2011 period. Analytical framework for the study include: Logistic Regression and Multiple Regression Models. Results show that access to mobile phones, using the internet to obtain information, and using the internet to send or receive mails were significant factors of the probability that a Nigerian chose agriculture or its related activities as a main occupation. Again, access to personal computers, use of the internet for e-banking, e-learning and for reading e-newspapers had significant impact on agricultural labour efficiency in Nigeria. The study recommends that labour policies should find a place for the role of ICTs, particularly the internet. JEL. Code: Q12